Effects of post-harvest storage on some biochemical parameters of different parts of two yams species (Dioscorea spp) - Kouakou DJE, Martin; Dabonne, Soumaila; Simplice Tagro Guehi; Lucien Patrice Kouame (Global Journal of Food and Agribusiness Management, 2010)
Some biochemical parameters of different parts of two varieties of edible yams tuber "Florido" (Dioscorea alata) and "Krenglè" (Dioscorea cayenensis-rotundata complex) were monitored during storage. The statistical analyses related to analysis of variance (ANOVA) and to principal component analysis (PCA) carried out on these eleven variables showed that the proximate and mineral composition of different parts of yam tuber were significantly different at 0.05 level between them and during the storage. Indeed, the dry matters, the reducing and total sugars contents increased significantly (P ≤ 0.05) during the conservation from month 0 to month 6 and varied from one tuber part to another. The dry matter content was highest in the proximal parts, while the reducing and total sugar contents were higher in the distal parts. The total phenolic compounds and all the studied minerals decreased significantly (P ≤ 0.05) during the conservation and varied from one tuber part to another. Contrary to these variables, the lipids and the crude protein contents didn’t vary significantly at 0.05 level from a tuber part to another one during the storage period which last six months.